2014
DOI: 10.3168/jds.2013-6978
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic variation of the udder of dairy ewes in early lactation and following an Escherichia coli endotoxin intramammary challenge in late lactation

Abstract: A total of 83 lactating dairy ewes (Manchega, n=48; Lacaune, n=35) were used in 2 consecutive experiments for assessing the ability of infrared thermography (IRT) to detect intramammary infections (IMI) by measuring udder skin temperatures (UST). In experiment 1, ewes were milked twice daily and IRT pictures of the udder were taken before and after milking at 46 and 56d in milk (DIM). Milk yield was 1.46 ± 0.04 L/d, on average. Detection of IMI was done using standard bacterial culture by udder half at 15, 34,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…Compared to TN-LPS, HS-LPS had or tended to have lower milk lactose at 4 to 8 h after LPS infusion (P = 0.011 to 0.072). The decrease in lactose content in LPS challenged mammary glands was also observed in dairy ewes 33 . The drop in lactose in milk is an indicator of tight-junction leakiness 35 since lactose partially moves to blood.…”
Section: Responses To Intramammary Lps Challenge Under Thermo-neutralmentioning
confidence: 60%
See 2 more Smart Citations
“…Compared to TN-LPS, HS-LPS had or tended to have lower milk lactose at 4 to 8 h after LPS infusion (P = 0.011 to 0.072). The decrease in lactose content in LPS challenged mammary glands was also observed in dairy ewes 33 . The drop in lactose in milk is an indicator of tight-junction leakiness 35 since lactose partially moves to blood.…”
Section: Responses To Intramammary Lps Challenge Under Thermo-neutralmentioning
confidence: 60%
“…The LPS challenge resulted in greater milk protein (3.72 vs. 3.08% for LPS and CON udder-halves, respectively; P < 0.01), whereas HS did not affect the milk protein (P = 0.188). Greater milk protein contents in LPS challenged mammary glands were also observed in dairy ewes 33 and cows 34 , which has been attributed to the influx of blood-borne proteins 34 . From 2 to 24 h the increment in milk protein caused by LPS injection was more marked in HS (+1.08 points) than in TN goats (+0.63 points).…”
Section: Responses To Intramammary Lps Challenge Under Thermo-neutralmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, IRT was found as a rapid and non–invasive cow-side technique for early detection of SCM in crossbred cows. Several studies demonstrated the use of IRT for early detection of SCM and clinical mastitis in dairy cows and ewes [8,11,14]. Skin temperature reflects the status of tissue metabolism, blood circulation, and abnormal thermal patterns can signify areas of superficial inflammation or circulatory impairments.…”
Section: Resultsmentioning
confidence: 99%
“…The statistical significance of these differences was not mentioned but based on reported figures, it could be determined that they were significant (P ≤ 0.05). A second study on the effect of various factors on udder SST in Manchega and Lacaune sheep (Castro-Costa et al 2014) revealed that the udder temperature measured using 55 × 40 pixel rectangles placed on both rear udder quarters significantly increased (by approx. 0.13°C) as a result of milking, which could be explained by the hyperaemia caused by the manipulation of the udder.…”
Section: Discussionmentioning
confidence: 99%